Fresh and hardened properties of concrete containing effective microorganisms. (January 2019) - Mohd.Sam, A R; Khanom, F; Kamaruzzaman, M; Md Tahir, M; Abdul Shukur Lim, N H; Awang, A Z; Ismail, A
Abstract: Nowadays, concrete is popularly used in many areas and applications in construction industry. If designed and manufactured properly it can be one of the most durable construction materials. However, during the life span of the structure the surrounding environment where the structure is built may pose long-term durability problem to concrete such as cracks and corrosion of steel reinforcement. Thus, researchers around the world continue searching for any possible means to improve concrete qualities. This paper presents study on the effects of Effective Microorganism on fresh and hardened properties of concrete. The percentage of Effective Microorganisms (EM) used in this study was 10% and incorporated in the concrete mix by replacing the water content. In this research work, a number of control and EM concrete cube samples were cast, cured in water and tested at the ages of 3, 7 and 28 days. The workability of fresh concrete was measured through the slump test. The effect of EM on hardened concrete was assessed through compression test and ultrasonic pulse velocity (UPV) test. The experimental result shows that the workability of concrete with EM was 67% higher than the control concrete. This may indicate that the EM has the potential to be used as workability enhancer. In terms of compressive strength, the EM concrete recorded 8% higher strength at 28 days compared to concrete without EM. In addition, the early strength of EM concrete was found to be higher by 41% and 27% at 3 and 7 days compared to control, respectively. The UPV result for EM concrete also shows higher value than control concrete indicating denser concrete. All experimental results indicated that the use of EM has positive effects on concrete properties.